The impact of altruism on brand attitude when moderated by religiosity: a preliminary study - Muklas, Dedi; Ma'ruf, Ma'ruf (INOVASI, 2020)
This study aims to examining the moderating role of religiosity toward causal relationship of altruism on brand attitude in grocery retailing from Muslim customers’ perspective. In this attempt, this study brought the specific context of West Sumatra as known province for religious community. This research adopted a survey approach where 110 questionnaires were obtained from selected grocery shoppers in Padang city, West Sumatra, Indonesia. The measurement of the constructs and their interrelationships were examined based on partial least squares structural equation modelling (PLS-SEM). Key findings of the research had revealed that religiosity didn't has the moderation effect, notwithstanding it still exert a significant influence over favorable brand attitude. As for altruism found to has significant impact on the generation of positive brand attitude. Based on the theory, egoism has always been the attentions of studies in understanding consumer's motivation in the research of consumer behavior. This study has added sufficient evidence on the area whether other human quality, namely altruism has significances toward consumer's overarching evaluation on a brand. Particularly in regard to consumers who possess a credence on Islamic teachings, referred to as Muslim.